Mechanistic insights of hepatoprotective effects of curcumin: Therapeutic updates and future prospects. (February 2019) - Khan, Haroon; Ullah, Hammad; Nabavi, Seyed M.
Abstract: The liver is the most essential organ of the body performing vital functions. Hepatic disorders affect the physiological and biochemical functions of the body. These disorders include hepatitis B, hepatitis C, alcoholic liver disease (ALD), nonalcoholic fatty liver disease (NAFLD), liver cirrhosis, hepatic failure and hepatocellular carcinoma (HCC). Drugs related hepatotoxicity is one of the major challenges facing by clinicians as it is a leading cause of liver failure. During post-marketing surveillance studies, detection and reporting of drug-induced hepatotoxicity may lead to drug withdrawal or warnings. Several mechanisms are involved in hepatotoxicity such as cell membrane disruption, initiating an immune response, alteration of cellular pathways of drug metabolism, accumulation of reactive oxygen species (ROS), lipid peroxidation and cell death. Curcumin, the active ingredient of turmeric and exhibits therapeutic potential for the treatment of diabetes, cardiovascular disorders and various types of cancers. Curcumin is strong anti-oxidant and anti-inflammatory effects and thus it possesses hepatoprotective properties. Despite its low bioavailability, its hepatoprotective effects have been studied in various protocols of hepatotoxicity including acetaminophen, alcohol, lindane, carbon tetrachloride (CCL4 ), diethylnitrosamine and heavy metals induced hepatotoxicities. This report reviews the hepatoprotective effects of curcumin with a focus on its mechanistic insights in various hepatotoxic protocols. Highlights: Hepatoxicity caused morbidity and mortality in millions of people around the world. Drug resistance and sensitivity with the classical treatments is a great challenge need to be address. Natural compound, curcumin has shown versatile hepatoprotective effects in different in vitro and in vivo models. Based on documented data, it could be the drug of future as a potent hepatoprotective agent after clinical confirmation.